The neural network for tool-related cognition: An activation likelihood estimation meta-analysis of 70 neuroimaging contrasts. Issue 3 (18th May 2016) - Ishibashi, Ryo; Pobric, Gorana; Saito, Satoru; Lambon Ralph, Matthew A.
ABSTRACT: The ability to recognize and use a variety of tools is an intriguing human cognitive function. Multiple neuroimaging studies have investigated neural activations with various types of tool-related tasks. In the present paper, we reviewed tool-related neural activations reported in 70 contrasts from 56 neuroimaging studies and performed a series of activation likelihood estimation (ALE) meta-analyses to identify tool-related cortical circuits dedicated either to general tool knowledge or to task-specific processes. The results indicate the following: (a) Common, task-general processing regions for tools are located in the left inferior parietal lobule (IPL) and ventral premotor cortex; and (b) task-specific regions are located in superior parietal lobule (SPL) and dorsal premotor area for imagining/executing actions with tools and in bilateral occipito-temporal cortex for recognizing/naming tools. The roles of these regions in task-general and task-specific activities are discussed with reference to evidence from neuropsychology, experimental psychology and other neuroimaging studies.